William Gilbert and esoteric Romanticism : a contextual study and annotated edition of The hurricane - Cheshire, Paul (Romantic reconfigurations., 2018)
This first annotated edition of William Gilbert's enigmatic poem, The Hurricane: a Theosophical and Western Eclogue, with extended interpretative chapters informed by Gilbert's magical and astrological writings, shows how its dark materials fed the imaginations of his friends Coleridge, Wordsworth and Southey, in their formative years between 1795 and 1798.